The Political Economy of Land Development In Nineteenth Century Toronto - Sanford, Barbara (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1987)
This paper challenges traditional ecological assumptions about urban growth and development by exploring the relationship between social structure and urban pattern. A neo-marxian analysis is used to examine the ways in which changing social, political and economic forces of Canadian society affected the distribution of social classes in urban space during three periods of Toronto's early growth; 1) the colonial period, 1791-1833; 2) the mercantile period, 1834-1850; and 3) the early industrial period, 1851-1881. The town's original land grants were allocated according to social status, physically expressing the hierarchical social structure of colonial life. Then, with the growing prosperity of local merchant capitalists, former regulations on land were abandoned in favour of speculative profits for individual property owners. Early street servicing and fire by-laws reinforced the existing micro-scale segregation. During capitalist industrialization the scale of segregation changed from the micro to the macro scale, with the development of working class districts and exclusive enclaves for the upper and middle classes. The latter were again reinforced with special provisions, suggesting that Toronto's social geography has historically been shaped by those with the power, wealth and position to protect and promote their own class interests.